Policy Impacts on Africa’s Extractive Sector: Botswana, Diamond Dependence, and Diversification in the Post-Diamond Period - Besada, Hany; O’Bright, Ben (Revue Gouvernance / Governance Review, 2018)
This paper investigates the topic of sustainable natural resource governance, and policy and politics thereof, in the context of Botswana. The authors endeavour to provide a preliminary justification for why Botswana, as a country of investigation, is a potential role model and a site of deep study for researchers of contemporary sustainable resource governance. This paper argues that the rest of Africa can learn from the Government of Botswana’s policies regarding multinational corporations operating in the mining sector, particularly in terms of attracting investment, but, too, Botswana could learn much from others in terms of economic diversification and linkage promotion.